The double-design dilemma: political science, parliamentary crisis and disciplinary justifications. Issue 2 (3rd April 2019) - Flinders, Matthew; Meakin, Alexandra; McCarthy Cotter, Leanne-Marie
ABSTRACT: Two separate, but inter-linked, dilemmas have highlighted the importance of design-led thinking. First, the crumbling physical fabric of the Palace of Westminster has prompted a multi-billion rebuilding project, which will require the parliamentary studies specialism to engage with questions of design, space, and architecture. Separately, political science more generally has been challenged to utilize the insights of design-thinking and design-practice: a challenge to which it is culturally and methodological ill-equipped. This article considers what a design-led approach to political science looks like in theory, and in practice, in the case study of the Restoration and Renewal of the Palace of Westminster. This represents a first attempt at how such a fusion could be beneficial for both politics as theory and politics as practice. The main conclusion is that although design-orientated political science is not a panacea for the challenges of modern democratic governance – in intellectual or practical terms – it does appear to offer significant potential in terms of theoretically-informed but solution focused research.